Gridlock depicting dysfunction in transport infrastructure through grids and metonymy - Ragasa, John David R.
This thesis was inspired by the deficiencies of Transport Infrastructure in the Philippines, particularly in Metro Manila. This thesis is concerned with tackling the narratives of subpar quality of roads, the abysmal waiting times for public transportation, and the painfully slow and delayed construction projects that promise efficiency. Such structures and experiences have become ubiquitous and commonplace to the FIlipino commuter and to the artist.